EDUKASI MOBILE TENTANG PHYSICAL DISTANCING UNTUK MENCEGAH PENYEBARAN COVID-19 DI WILAYAH KERJA PUSKESMAS TANARA DESA LEMPUYANG KECAMATAN TANARA KABUPATEN SERANG - Hamdiah, Dedeh; Suryati, Eti; Umar, Ernawati (Universitas Sultan Ageng Tirtayasa, 2021)
Physical distancing is the act of maintaining physical distance between one person and another. This was done to prevent the spread of Covid-19. The purpose of this PPM is to provide mobile education about physical distancing to prevent the spread of Covid-19 so that people understand about physical distancing to prevent the spread of Covid-19. The method used is mobile education using four-wheeled vehicles. The results achieved were that the community understood the meaning of physical distancing, the purpose of physical distancing and how to carry out physical distancing to prevent the spread of Covid-19. Good public knowledge is the highest proportion at 89% compared to poor public knowledge, which is 11%. This activity is carried out in the work area of the Tanara Community Health Center, Lempuyang Village, Tanara District, Serang Regency.